PENGARUH PENGGUNAAN GADGET TERHADAP KESEHATAN MENTAL SISWA SMK - Alam Pangestu, Shakti; Sabir, Arisman; Fauziah; Larisman, Larisman; Hayati, Amal (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
This study is motivated by the issue of delays and absenteeism among students at SMK Negeri 3 Bungo, which is largely influenced by excessive gadget use, especially for social media and online games. Uncontrolled gadget usage leads to sleep problems, stress, and concentration issues that affect attendance and punctuality. This research aims to observe the impact of gadget use on mental health at SMK Negeri 3 Bungo. This study employs a descriptive quantitative method to determine whether there is a causal relationship between gadget use and mental health at SMK Negeri 3 Bungo. The scale used is the ordinal scale, with the sample consisting of class X.TAV students from SMK Negeri 3 Bungo, selected using the Cluster Random Sampling technique. Data collection was done using questionnaires, and data analysis was performed using hypothesis testing or ANOVA. The research results show that gadget use has an impact on mental health at SMK Negeri 3 Bungo. The calculated t-value for the gadget use variable is 6.249, which is greater than the t-table value of 1.690, indicating that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. This means,